Identification of a class of index models: A topological approach. Issue 1 (17th June 2020) - Fosgerau, Mogens; Kristensen, Dennis
Summary: We establish nonparametric identification in a class of so-called index models by using a novel approach that relies on general topological results. Our proof strategy requires substantially weaker conditions on the functions and distributions characterising the model than those required by existing strategies; in particular, it does not require any large-support conditions on the regressors of our model. We apply the general identification result to additive random utility and competing risk models.